Sustainable Agroforestry Sustainable Agroforestry Model for Supporting Farming Communities by Identifying Land Development in Bone District - Dahliana, Besse; Wahana, Syainullah; Djabar, Murni (Teumulong: Journal of Community Service, 2024)
Agroforestry is an optimal land management approach that combines forestry, agriculture, livestock, and fisheries activities within the same area. Sustainable agroforestry models are implemented through community support in Bone District. The Bengo region is one of the initiatives undertaken by STIP YAPI BONE as part of a partnership scheme for the Agroforestry model, which represents a local wisdom aimed at safeguarding water sources by integrating several key components, including food crops, perennial plants, and livestock. It is undeniable that the Bengo region is highly unique, as it is divided into several zones, such as the core zone (Integrated Agrocomplex Gardens), buffer zone (Land for Integrated Forestry, Plantation, Agriculture, and Fisheries Commodities), and utilization zone. It holds significant social, cultural, economic, and ecological value. Bengo boasts two key farmers, Mr. Sahir and Mr. Asgar, who have successfully transformed their cocoa plantations into Agroforestry gardens. Therefore, Bengo has the potential to become a cornerstone for the partnership between the Research and Community Service Institution, offering economic, social, and ecological benefits. Hence, it is imperative to preserve Bengo. One approach to achieving this is to raise awareness among all stakeholders, including both the community and the government, regarding the importance of applying Sustainable Agroforestry models to critical lands in Bone District, particularly in South Sulawesi.